Representation of Bengkulu Provincial DPRD Members in Supporting the Government's “Help the People” Policy - Eceh Trisna Ayuh; Marlinda Irwanti; Siti Nabila Ria (Yayasan Darussalam Bengkulu, 2026)
Regional legislative bodies (DPRD) play a strategic yet underexamined role in ensuring welfare-oriented policies genuinely benefit the public. This study analyzes the representation of Bengkulu Provincial DPRD members in supporting the